The use of respirometry as a tool for the diagnosis of waste water treatment plants. A real case study in Southern Spain. - Arias-Navarro, María; Villén-Guzmán, María Dolores; Pérez-Recuerda, Rocío; Rodríguez-Maroto, José Miguel (Elsevier, 2019)
The influence of operating conditions of wastewater treatment plants in microbial composition of activated sludge should be controlled to evaluate the efficiency of the plant. Respirometry has been widely applied as a useful tool for a better understanding of the processes taking place in activated sludge system. In the present study, respirometry tests have provided relevant information about possible faults in the plant and potential improvements. With this aim, experimental tests were applied to a real wastewater treatment plant serving an equivalent population of 730,000. To evaluate the sludge activated process, the samples of mixed liquor studied were: those collected from inlet and outlet flow of reactor system and the laboratory prepared samples from mixing those from the influent/effluent wastewater to/from reactor with the returned activated sludge. The comparison of reference values with experimental results of factor charge (0.9–1.5), organic loading rate (>0.5 gBODgMLVSS−1 d−1) and specific oxygen uptake rate in mixed liquor for outlet samples from reactor (mainly > 10 mgO2 g-1  h−1) obtained from respirometry tests revealed that the plant was operated at low efficiency and at overload. These conditions have a direct influence on the efficiency of biological treatment and the secondary clarifier operation. The sedimentation of activated sludge was evaluated through the determination of the sludge volume index during 10 months obtaining an average value of 208 mL g−1. Respirometry tests also revealed that the decrease of biomass activity was associated with the wastewater instead of with the biomass.
https://openpolicyfinder.jisc.ac.uk/id/publication/33322
Keywords: Plantas depuradoras de agua; Agua potable; Respirometry; WWTP optimization; WWTP diagnosis